Comparison of two blind brachial plexus blocks in goat cadavers. - Sirimongkolvorakul , Sunisa; Sornphu, Tanasid (Journal of Advanced Veterinary and Animal Research, 2025)
Objective: This study aimed to compare two approaches to the brachial plexus: the traditional blind method and an additional technique, both of which use anatomical landmarks to guide needle insertion. Materials and Methods: The traditional and additional approaches were performed on both thoracic limbs of 24 cadavers (24 for each approach). Methylene dye is used for injection and nerve staining. We counted the nerves that successfully stained (staining less than 1 cm). The Mann– Whitney U test was used to compare approaches. Results: The findings indicated that all cadavers were successfully used. The traditional approach and the additional approach revealed success rates of 45.83% and 54.17%, respectively. We found no significant differences between the two techniques (p > 0.05). Conclusion: The additional approach presents a viable alternative to the traditional method for performing the brachial plexus block in goats. Further research into the clinical differences between these techniques could lead to useful insights that help make them more accurate and useful. J. Adv. Vet. Anim. Res., 12(1): 64–69, March 2025 http://doi.org/10.5455/javar.2025.l872